Mental Health Of International Students During The Covid-19 Pandemic - Aisha Musse, Mohamud (Universiti Malaysia Sarawak (UNIMAS), 2022)
This study aimed to explore the experience of international students along with possible mental struggles faced by international students throughout the COVID-19 pandemic. Moreover, this purpose of this study is to identify the coping mechanisms utilized by international students in the midst of COVID-19 pandemic. The coronavirus was first detected in Wuhan, China in late December of 2019. In the following year, the WHO has officially declared a pandemic which led to multiple countries going in nationwide lockdown and mandating masks. In Malaysia, the movement control order (MCO) was first imposed by the Malaysian government for two weeks. However, coronavirus cases have yet to slow down which lead to multiple extensions of the MCO. With universities switching to online learning as an attempt to reduce the number of infections, many international students abroad are left stranded in a foreign country where they are not able to return home to visit their families.